Kredi hacminin para arzı ve ekonomik büyüme üzerine etkisi - Kamacı, Ahmet; Ceyhan, M. Said; Peçe, Mehmet Akif; Ceyhan, Said; Peçe, Mehmet Akif (Uluslararası Yönetim İktisat ve İşletme Dergisi, 2017)
The banks that undertake financial intermediation provide the increase of production, employment and economic growth with the credits they give. The increase in the credit volume of the banks leads to an increase in the money supply in the economy, which will result in an increase in economic growth. For this reason, the relation between bank loans and economic growth has been examined in many studies. This study examines the impact of credit volume on money supply and economic growth in Turkey. 2005: Q4-2017: FMOLS and DOLS tests showing cointegration, causality and coefficient of correlation for period three-month time series were performed. According to the findings of the study, there is a one-way causality relation from the money supply to the domestic credit volume and from the economic growth to the domestic credit volume. At the same time, the among money supply, economic growth and volume of domestic credit was identified a long-run cointegrated relationship. FMOLS and DOLS tests also support Granger causality results. According to the FMOLS test, a 1% increase in the volume of domestic credit increases the money supply by 0.67% (0.66% compared to DOLS). In terms of economic growth; According to the FMOLS test, a 1% increase in the volume of domestic credit increases economic growth by 0.22% (0.23% compared to DOLS)

Finansal aracılık görevini üstlenen bankalar, verdikleri kredilerle hem üretimin, hem istihdamın, hem de ekonomik büyümenin artmasını sağlamaktadır. Bankaların kredi hacminin artması, ekonomideki para arzının artışına yol açar, bu durum da ekonomik büyümenin artması sonucunu doğuracaktır. Bu nedenle, banka kredileri ile ekonomik büyüme ilişkisi birçok çalışmada incelenmiştir. Bu çalışmada, Türkiye’de kredi hacminin para arzı ve ekonomik büyüme üzerindeki etkisi incelenmiştir. 2005:Q4-2017:Q1 dönemi için üçer aylık zaman serisini içeren veriler için, eşbütünleşme, nedensellik ve ilişkinin katsayısını gösteren FMOLS ve DOLS testleri yapılmıştır. Çalışmadan elde edilen bulgulara göre, para arzından yurtiçi kredi hacmine doğru tek yönlü ve ekonomik büyümeden yurtiçi kredi hacmine doğru yine tek yönlü bir nedensel ilişki mevcuttur. Aynı zamanda yurtiçi kredi hacmiyle para arzı ve ekonomik büyüme arasında uzun dönemli eşbütünleşik bir ilişki tespit edilmiştir. FMOLS ve DOLS tes-tleri de Granger nedensellik sonuçlarını desteklemektedir. FMOLS testine göre, yurtiçi kredi hacmindeki % 1’lik artış para arzını % 0,67 (DOLS’ye göre %0,66) arttırmaktadır. Ekonomik büyüme açısından baktığımızda ise; FMOLS testine göre, yurtiçi kredi hacmindeki % 1’lik artış ekonomik büyümeyi % 0,22 (DOLS’ye göre % 0,23) arttırmaktadır.
Keywords: Kredi hacmi; Para arzı; Ekonomik büyüme; Nedensellik; Loan volume; Money supply; Economic growth; Causality